LAW, VIRTUE AND SUBJECTIVITY: JUSTICE AND ETHICAL FORMATION IN BOOK V OF THE NICOMACHEAN ETHICS - Silva, Juscelino; Albuquerque, Rafael Raimundo Oliveira; Barros, Edson da Silva; da Silva, Thayline Pereira; Viana, Roseane Henrique; Neves, Cezar Ricardo Lima; dos Santos, José Domingos Alves; Costa, Nubia Silva (Seven Editora, 2026)
This article examines the relationship between law and subjectivity based on Book V of Aristotle’s Nicomachean Ethics, focusing on the articulation between legal normativity and the ethical formation of the subject. The central problem addressed concerns how legal justice depends on previously constituted subjective dispositions and to what extent the effectiveness of law presupposes an ethical education of the psychē. The guiding hypothesis is that, in Aristotle, law (nomos) does not operate autonomously, but achieves effectiveness through its mediation with habit (hexis) and the containment of excess (hybris), revealing a mutual implication between legal order and moral subjectivity. Methodologically, the study adopts a philosophical-hermeneutical reading of Book V, structured around three conceptual triads: nomos–hexis–hybris, aretē–dikē–adikia, and dikaiosynē–dikaion–dikaios. The analysis demonstrates that Aristotelian justice cannot be reduced to formal legality, since it requires the integration of law, virtue, and prudent judgment, thereby assigning a constitutive role to subjectivity in the realization of justice. The article concludes that this perspective offers a significant contribution to legal philosophy by showing that the legitimacy and effectiveness of legal norms depend on their alignment with ethical formation and the ethos of the political community.